2020
DOI: 10.1039/c9py01129c
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide-mediated polymerisation of thioacrylates and their transformation into poly(acrylamide)s

Abstract: Nitroxide mediated polymers of thioacrylates can be transformed into poly(acrylamide)s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…We will discuss the cloud points of the polymers later. According to the literature, the polymer chain remains intact under the side-chain ester to amide transformation. , Furthermore, we started with very low Mw PAA (2000 g/mol), which is within the window for an optimum chain length for KHI polymers. If there had been significant polymer degradation, the chain length would have decreased to a level that shows a very poor KHI effect (usually <ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will discuss the cloud points of the polymers later. According to the literature, the polymer chain remains intact under the side-chain ester to amide transformation. , Furthermore, we started with very low Mw PAA (2000 g/mol), which is within the window for an optimum chain length for KHI polymers. If there had been significant polymer degradation, the chain length would have decreased to a level that shows a very poor KHI effect (usually <ca.…”
Section: Methodsmentioning
confidence: 99%
“…More recent research has showed that it is possible to make poly­(acrylamide)­s from poly­(thioacrylate)­s via an amidation reaction . The authors obtained full amidation conversion of poly­( N -benzyl acrylamide) and poly­( N -isopropylacrylamide) from poly­(ethyl thioacrylate) reacted with benzylamine and isopropylamine after 48 h.…”
Section: Introductionmentioning
confidence: 99%
“…Kişisel harcama vergisinin artan oranlı uygulanması ve vergi ödeme gücüne ulaşabilmek için her türlü indirim ve istisna uygulamasına olanak tanıması, enflasyonla mücadelede de etkili bir biçimde kullanılabilmesini sağlamaktadır 38 . Buna istinaden, tasarrufları teşvik eden ve harcamaları yüksek oranda vergileyerek sınırlayan yapısıyla, kişisel harcama vergisi talepten kaynaklanan enflasyonu doğrudan kontrol altında tutan etkin bir vergileme aracı olarak kullanılabilmektedir 39 .…”
Section: Cki̇şi̇sel Harcama Vergi̇si̇ni̇n Ekonomi̇k İsti̇krar üZeri̇ndeki̇ Etki̇leri̇unclassified
“…Reversible Deactivation Radical Polymerization (RDRP) methods, including atom-transfer radical polymerization (ATRP), 1,2 single electron transfer-living radical polymerization (SET-LRP), 3,4 reversible addition-fragmentation chain-transfer polymerization (RAFT) 5,6 and nitroxide-mediated polymerization (NMP) [7][8][9] have provided access to an increasing range of well-dened materials with sophisticated architectures, various functionalities and controlled (macro)molecular characteristics. [10][11][12] Until recently, a notable hindrance for their development has been oxygen intolerance.…”
Section: Introductionmentioning
confidence: 99%